DETERMINATION OF CATCH COMPOSITION IN THE BOTTOM TRAWLING USING MULTIVARIATE STATISTICAL METHODS IN EASTERN MEDITERRANEAN - Sangun, Levent; Basusta, Nuni; Guney, O. Inanc (Parlar Scientific Publications (P S P), 2018)
This study determines the catch composition of fish caught by commercial trawling in the Northeastern Mediterranean throughout the 2012 - 2013 fishing season. An analysis of the reliability of trawl catch subsamples found the Cronbach's Alpha value to be 0.73, which indicates the sampling was accurate. The highest CPUE value was recorded at 31.12 kg/hour(-1) in September, with the lowest recorded at 11.87 kg/hour(-1) in March and the mean CPUE value is 18.14 +/- 6.68 kg/hour(-1). Principal components analysis (PCA), hierarchical cluster analysis (HCA) and factor analysis (FA) were performed respectively to determine the catch composition. The analyses accounted for the 85% of total variance, with six factors in FA, a single component in PCA, and 10 clusters in HCA. Each of the three methods found the percentages of the most frequent four species in the catch composition to be 21.7% for Saurida undosquamis, 17.5% for Mullus barbatus, 7.73% for Upeneus moluccensis, and 7.21% for Boops boops. Two of these are lessepsian species.
Keywords: Catch composition; hierarchical cluster analysis; factor analysis; principal components analysis; CPUE